Managing Self Harm in Schools: A Multi-Agency View - Alderton, Joanne (2011)
The current study is concerned with how schools and staff manage students who self-harm. It is recognised that there are major issues within the current research literature regarding the various definitions of self-harm, the variety of methodology in the research and therefore, in the results and theories generated. The current literature is relatively new due to the increasing public awareness of self-harming behaviour and is therefore, in early development.